1984
DOI: 10.1164/arrd.1984.129.5.790
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Correlation of Physiologic Changes Caused by SO2-induced Bronchitis in Dogs

Abstract: Chronic bronchitis was induced in 6 mongrel dogs by exposure to SO2 gas for 6 to 18 months. All of the dogs developed cough and mucus hypersecretion. Chronic airway obstruction and decreased airway responsiveness to inhaled histamine developed in 5 of the dogs. Histologic changes in dogs evaluated after SO2 exposure included significant mucous gland hypertrophy and hyperplasia, epithelial thickening, and a decrease in the number of luminal cells containing undischarged secretory granules. Acute and chronic inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…The preaccident level was never reached, however. Chronic obstructive pulmonary disease developed as a sequela of exposure to high concentrations of sulfur dioxide, as documented also in case reports (10,12,18) and as induced experimentally in animals (13,14,15,16). Bronchial hyperresponsiviness seems to persist for years in humans exposed to high concentrations of sulfur dioxide.…”
Section: Discussionmentioning
confidence: 66%
“…The preaccident level was never reached, however. Chronic obstructive pulmonary disease developed as a sequela of exposure to high concentrations of sulfur dioxide, as documented also in case reports (10,12,18) and as induced experimentally in animals (13,14,15,16). Bronchial hyperresponsiviness seems to persist for years in humans exposed to high concentrations of sulfur dioxide.…”
Section: Discussionmentioning
confidence: 66%
“…The airway inflammation, evaluated by the number of bronchoalveolar lavage cells and the percentage of neutrophils in bronchoalveolar cells, is closely paralleled by the development of airway hyperresponsiveness in the presented model. Although some studies have demonstrated that neutrophil infiltration into the airways is not necessary for an increase in airway responsiveness (25,26), the hypothesis that neutrophil infiltration alters airway function is, however, supported by a larger number of studies (27)(28)(29). We hypothesize that this leukocyte accumulation, dominated by the infiltration of neutrophils, will lead to the induction of in vivo airway hyperresponsiveness and in vitro tracheal hyperreactivity.…”
Section: Discussionmentioning
confidence: 86%
“…Sulfur dioxide exposure induces superficial secretory cell hyperplasia in rats (145) and mucus gland hypertrophy in dogs (236). Ozone induces mucus cell metaplasia in rat nasal airway epithelium (106).…”
Section: Mucin Regulation By Inflammatory Mediators In Vitro and In Vmentioning
confidence: 99%